Molecular Detection of Some Virulence Genes of Methicillin Resistant Staphylococcus Aureus Clinical Isolates in Diyala Province - Hind Mohammed Jasim, Zainab Mohammed Alzubaidy (Pakistan Journal of Medical & Health Sciences, 2022)
In this study a total of (264) clinical samples were collected from patients with different infections from Baquba and Al Batool Teaching Hospitals during the period from September 2021 to April 2022. The results demonstrated that 50(26.4%) of the isolates were S.aureus distributed according to the sources as follows: wound13 (26%), urine11 (22%), vaginal swab10 (20%), blood8 (16%), and burn8 (16%) by using blood agar and mannitol salt agar, microscopic characteristics, biochemical tests, Vitek-2 system. All the (50) isolates showed catalase positive and oxidase negative. On baired parker agar showed black, convex, and shiny colonies which approve the presence of S. aureus with a clear zone 34(68%) confirm coagulase-positive and 16(32%) of the isolates without a clear zone that confirms coagulase-negative. The detection of some virulence factors as ESBL 2%, Dnase 62%, gelatinase 42%, Beta hemolysin 82%, and 2% MBL. Biofilm formation was detected by Microtiter plate method: strong14%, moderate42%, and 44% weak. The antibiotic susceptibility tests against 16 different types of antibiotics by the Kirby Bauer disc diffusion method reported that the isolates were resistant to Oxacillin (98%), Vancomycin and Nitrofurantoin (100%) Netilimycin (14%) Amikacin and tetracycline (52%), Azithromycin (78%), Ciprofloxacin(62%), Levofloxacin(42%), Clindamycin(80%), Chloramphenicol(32%), Ofloxacin(40%), Gentamycin(56%), Teicoplanin(90%), Clarithromycin(74%), Imipenem(44%). The result showed 41(82%) multidrug resistance (MDR), 7 (14%) as extensive drug resistance (XDR), and the remaining 2(4%) pan drug resistance (PDR). The minimum inhibitory concentration (MIC) was determined against vancomycin and azithromycin for seven isolates (strong biofilm formation) recorded that (16-1024) µg/ml for Vancomycin while the bacteria showed highly resist to Azithromycin. A polymerase Chain Reaction was performed for the detection of mecA and icaADB were detected in all seven isolates (100%), while coa and spa genes appeared (71.4%) in five isolates.